DEVELOPING A METHODOLOGICAL SYSTEM FOR EVALUATING THE IMPLEMENTATION OF ISO/IEC 17025 REQUIREMENTS IN CALIBRATION LABORATORIES FOR GEOMETRIC MEASURING INSTRUMENTS - Shertoylokova Gavkharoy Numonjon qizi,; Shertoylokova Gavkharoy Numonjon qizi,; Najmiddin Muminov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In the rapidly evolving landscape of industry and science, accuracy and reliability have become core values in every technical process. Calibration laboratories that work specifically with geometric measuring instruments play a key role in supplying these values, as the precision of measurement results impacts not only product quality but also the technological reputation of manufacturers at local and international levels. At the heart of guaranteeing this precision stands adherence to the ISO/IEC 17025 standard, a globally recognized benchmark for the competence of testing and calibration laboratories. However, merely declaring compliance with the standard is insufficient; there must be a well-developed methodological system to conduct regular, thorough evaluations of how well laboratories actually fulfill ISO/IEC 17025 requirements in their everyday actions and documentation.